HUBUNGAN TINGKAT PENDIDIKAN DAN TANGGUNG JAWAB LINGKUNGAN DENGAN PARTISIPASI PEMELIHARAAN KESEHATAN LINGKUNGAN - Mpa Saputra (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2016)
The Objective of the research is to determine the relationship between the level of education the community Bojong Rawa village and environmental responsibility with the participation of the health maintenance environment. The method which is used in this research is the correlation associative quantitative approach of 60 people a total sample. Data were collected through questionnaires. Analysis of data to test the hypothesis of research is used the regression analysis. The research concluded that; First, there is a positive relationship between the level of education with the participation of the health maintenance environment with the correllation coefficient of 0, 86 at = 0, 05 on = 39, 71 + 3, 191 X1 the regression equation. Second, have a positive relationship between environmental responsibility and participation of the healthmaintenance environment with the correlation regression equation. Third, there is a positive relationship between the level of education and environmental responsibility together with the participation of the health maintenance environment with multiple correlation coefficient () of () with coefficients of determination of 96 %. The double regression equation = - 0, 7 + - 0, 64 + 1, 13.